Factors Influencing Learners’ Participation in Physical Education in The New Normal: An Input to Curriculum Development Program - Josephine R Alcantara; Alberto D Yazon; Consorcia S Tan; Lerma P Buenvinida; Marcial M Bandoy (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
This study focused on determining the factors that influence the learners’ participation in Physical Education (PE) under the New Normal; it also investigated perceptions about teaching quality, level of readiness in distance learning, and the mean level of participation in PE in accordance to MELCS. It further looked into the significant relationships between factors of teaching quality; learners’ level of readiness to distance learning as against learners’ participation; and learners’ demography. This study offers a lot of learning opportunities about simplified and essential teaching modalities, which are focused and easy for learners, under the New Normal environment and under the threat of being infected with Covid-19. Frequencies, percentage, means, standard deviation, Pearson product moment of correlation, multiple linear regression, and hierarchical linear regression were the statistical tools applied in the analysis of data collected from selected Junior High School learners from 25 districts in the Division of Laguna. Major findings from the study are that (i) learners have a high level of perception of teaching quality in terms of cognitive activation, supportive climate, and classroom management; (ii) learners have a high level of readiness on distance learning in terms of availability of technology, use of technology, self-confidence, acceptance, and time management skills; and (iii) a high mean level on learner’s participation in PE according to their respective MELCS in terms of personalized exercise programs, physical activity participation, physical activity/fitness assessment, and skills demonstration. This study recommended that physical education teachers may provide students with more enhanced and localized activities that are tailored to their interests and appropriate for this new normal setting.